2020
DOI: 10.3329/bjpt.v27i1.47564
|View full text |Cite
|
Sign up to set email alerts
|

Leaf architecture and petiole anatomy of Philippine Dipterocarpus species (Dipterocarpaceae)

Abstract: The study investigated the leaf architecture and petiole anatomy of eight Dipterocarpus (Dipterocarpaceae) species growing in Mount Makiling Forest Reserve (MMFR) in the Philippines to delineate the species, especially during their non-flowering phase. Leaf and petiole samples from MMFR were examined following the manual on leaf architecture studies. Freehand technique was used to examine the stomata and petiole characters. A UPGMA phenogram was then generated to determine the relationships among Dipterocarpus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, the determination key was formulated based on leaf architecture character. This analysis commonly used in clustering especially using morphological data (Hernandez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the determination key was formulated based on leaf architecture character. This analysis commonly used in clustering especially using morphological data (Hernandez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The petiole anatomy has proven to be useful as an identification tool in Shorea spp. (Hernandez et al 2020). Several Shorea species and Dipterocarpus gracilis have slightly geniculate petiole.…”
Section: Leaf Character Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have showed that these distinctive characters can be used as taxonomic characters at species level. For instance, distinct areolation among species have been reported to be one of the most useful leaf characters used as taxonomic tool for delimitation, as seen in the study of Khaya species by Oyedapo et al (2018) and Philippine Dipterocarpus species by Hernandez et al (2020). Moreover, taxonomic significance of leaf apex shape and size have also been elucidated by studies of Shorea species by Khan et al (2016) and Pulan and Buot (2014).…”
Section: Leaf Characteristics Of S Aqueum S Samarangense and P Guajavamentioning
confidence: 99%
“…The leaves were photo-scanned using an HP LaserJet scanner (M1132 MFP, Palo Alto, CA, USA) with a 600 dpi resolution. ImageJ processing software was used to analyze the LA of the samples collected following the procedures in Schneider et al [51] and the modified procedure in Hernandez et al [52].…”
Section: Measurements Of Morphophysiological Traitsmentioning
confidence: 99%